The Irrational Beliefs and their Relation to the Level of Aspiration among Orphanage Teenagers in Makkah - Falattah, Nahlah Talal; Al -Sharif, Laila Mubarak (Journal of Educational and Psychological Sciences, 2021)
The aim of this study was to identify the relationship between irrational beliefs and the level of aspiration among orphan's teenagers in Makkah, The study also aimed to identify the differences between the teenagers average scores on some dimensions of a scale of level of aspiration according to (level- age), the study sample consisted of all teenager girls who were in an orphan house in Makkah called “Dar Alzhour”; they were 29 teenagers. The researchers used descriptive and comparative research design, a scale of irrational ideas; prepared by Motaaz Abdullah and Mohamd Abdulrhman (2002) and developed by the researcher, was used alongside with the scale of level of aspiration; prepared by Amal Bathah (2004) and developed by the researcher. The two scales were tested and validated in both had high level of validity and reliability. The research results showed that the average of the irrational ideas spread among the study sample was (3.38) which was average score, whereas the average of the level of aspiration was (3.48) which was a high score. There was no statistically significant relationship between the irrational beliefs and level of aspiration among the study sample, there was no statistically significant differences in the means at the degree of irrational beliefs according to (level- age), and there was no statistically significant relationship the means at the degree of aspiration level according to (level- age). The important recommendations of the researcher were as follows: to focus on preventive counseling programs aimed at educating rational and logical thinking among orphans as part of the personality education and mental health programs, to adopt modern trends in psychosocial treatment when dealing with orphans' problems, to pay attention to the employment of specialists who are prepared and qualified professionally and ethically, to investigate the surrogate mother before handing over work, and finally, to involve orphans in identifying programs and activities that reflect their needs, and integrate them into society from an early age.
Keywords: Irrational Beliefs; Level of Aspiration; Teenagers; Orphan